Diamond Fraud Elements: Implication Of Fraud Indications On Preparation Of Financial Report - Fera Tjahjani; Yullyana Mulyadi; Widanarni Pujiastuti (Jurnalku, 2022)
This research aims to explore fraud diamond elements to detect fraud indications in financial statement. Samples were taken from 32 state owned enterprises of Indonesia which published audited financial statement from 2016 to 2018. The hypothesis in this study were tested by Benish M-score model. Fraud diamond elements are financial stability measured by assets change, financial pressure measured by return on assets, external pressure measured by leverage, nature of industry measured by receivable, ineffective monitoring measured by independent commissioners, rationalization measured by total accrual to total assets and capability measured by change of directors. Nature of industry has positive effect to fraud indications in financial statement while the rest six elements have no influences.